The journalist facing technology: an approach to the technological skills needed for digital journalism - Farina Ojeda, Héctor Claudio (2020)
In the context of the transformations of journalism through the Internet, technological innovation and changes in audiences’ information consumption behavior, journalists need to develop skills in the use of technology in order to meet the requirements of the profession. In this article we propose to identify some of the technological skills needed by journalists, for which we conducted interviews with editors and reporters of Mexican newspapers.